Desentralisasi dan Ketimpangan Pembangunan Antar Daerah - Mu’minah, Sulton; Tjenreng, M. B. Zubakhrum (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This study aims to analyze the role of decentralization in promoting regional development and reducing interregional inequality. The research employs a qualitative descriptive approach by analyzing secondary data and reviewing relevant literature to identify factors affecting the effectiveness of decentralization. The results reveal that although decentralization has enhanced regional autonomy and development capacity, its impact on reducing inequality remains limited. Findings indicate that discrepancies in fiscal capacity, uneven infrastructure distribution, and varying quality of human resources are major obstacles to balanced development. In brief, while decentralization contributes positively to regional development, integrated efforts such as capacity building, infrastructure improvement, and targeted fiscal policies are necessary to significantly reduce inequality.